1994
DOI: 10.1002/stem.5530120504
|View full text |Cite
|
Sign up to set email alerts
|

Intensive therapy and autotransplantation in hodgkin's disease

Abstract: Intensive therapy and autologous marrow or peripheral blood stem cell transplantation is often utilized in Hodgkin's disease patients whose disease has progressed after primary conventional chemotherapy. A number of studies have described long-term disease-free survival in up to 50% of transplanted patients. High-dose chemotherapy conditioning regimens such as "CBV" or "BEAM" have been used more often than regimens containing total body irradiation. Usually unpurged autologous bone marrow has been utilized as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…1,2 Also other strategies of antineoplastic therapy may cause cardiotoxicity of a clinical significance, as exemplified by cyclophosphamide treatment in patients with malignant lymphoma. 3,4 Nevertheless, clinical observations suggest that cardiovascular complications may appear in some patients in a course of peripheral blood (PB) stem cell transplantation and also there is a serious risk of developing some long-term complications. In hematological malignancies, sustained remissions and even cures may be achieved in certain patients by use of HSCT following the high-dose chemotherapy (HDC).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Also other strategies of antineoplastic therapy may cause cardiotoxicity of a clinical significance, as exemplified by cyclophosphamide treatment in patients with malignant lymphoma. 3,4 Nevertheless, clinical observations suggest that cardiovascular complications may appear in some patients in a course of peripheral blood (PB) stem cell transplantation and also there is a serious risk of developing some long-term complications. In hematological malignancies, sustained remissions and even cures may be achieved in certain patients by use of HSCT following the high-dose chemotherapy (HDC).…”
mentioning
confidence: 99%
“…In hematological malignancies, sustained remissions and even cures may be achieved in certain patients by use of HSCT following the high-dose chemotherapy (HDC). 3,4 Nevertheless, clinical observations suggest that cardiovascular complications may appear in some patients in a course of peripheral blood (PB) stem cell transplantation and also there is a serious risk of developing some long-term complications. Until now, a detailed range of possible cardiovascular complications and potential cardiotoxic effects of stem cells administration in individual groups of patients remains unknown.…”
mentioning
confidence: 99%
“…Data presented in a number of studies (41)(42)(43)(44)(45) have demonstrated a long-term disease-free survival of Recently, autologous blood stem cells have been utilized in cases where potential harvest sites (hips) have been irradiated. Results from two larger series suggest that some patients may become cured (46,47).…”
Section: Hodgkin's Diseasementioning
confidence: 98%
“…The main innovation between 1970 and 2005 was high-dose chemotherapy combined with peripheral blood stem cell transplantation for those whose disease was not responding to conventional chemotherapy 42. This was introduced in the late 1980s and 1990s, with considerable variation between countries (table 1).…”
Section: Four Illustrationsmentioning
confidence: 99%